Produksi dan Kandungan Nutrien Beberapa Varietas Sorgum Hybrid dengan Jarak Tanam Berbeda sebagai Sumber Pakan - H Hajar; L Abdullah; D Diapari (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2019)
Sorghum feed is a type of cereal plant that has potential use as animal feed or forage. The reseach aim was to evaluate production and nutritional quality of some sorghum hybrid varieties, and determined the optimal spacing of sorghum plants. This research was arranged in a factorial randomized block design with 6 treatments and four replications. The first factor was the varieties of 12FS9006, 13FB7001 and 12S49001. The second factor was space of 25x25 cm and 25x40 cm. The variables were fresh and dry matter of biomass production and also nutrient (ash, crude fiber, crude protein, Neutral Detergen Fiber and Acid Detergen Fiber. Sorghum varieties had significant effect (p<0.05) to fresh biomass production, dry matter biomass production, ash, crude fiber and crude protein). The space had a significant effect (p<0.05) to the dry matter production of biomass and crude fiber. The average variety of fresh biomass plant production was (18.90 tons ha-1), dry matter production of biomass was (4 ton ha-1), ash (5.51%), crude fiber (30.90%) and crude protein (8.45%). The average dry matter production was 4.34 tons ha-1 and crude fiber 29.96%. It can be concluded that the highest production and the best nutrient quality of sorghum hybrid was obtained at the sorghum variety of 12S49001, the distance of 25x25 cm was the best plant space for hybrid sorghum production. Keywords: hybrid varieties, nutrient, plant space, production